2014
DOI: 10.1371/journal.pone.0098440
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IL-1β and IL-17A Driven Inflammation during Influenza-Induced Exacerbations of Chronic Lung Inflammation

Abstract: For patients with chronic lung diseases, such as chronic obstructive pulmonary disease (COPD), exacerbations are life-threatening events causing acute respiratory distress that can even lead to hospitalization and death. Although a great deal of effort has been put into research of exacerbations and potential treatment options, the exact underlying mechanisms are yet to be deciphered and no therapy that effectively targets the excessive inflammation is available. In this study, we report that interleukin-1β (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…The effects of cytokine synergism have been reported in various host cellular responses. Synergistic effects of IL-1b, IL-6 and TNF-a on inflammatory and stress mediators [22] and IL-1b and IL-17 on chronic lung inflammation after viral infection [23] have been reported. In particular, the interaction between IL-1b and IL-6 in many types of inflammation [24][25][26] and the mechanisms of synergism [27][28][29] have been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of cytokine synergism have been reported in various host cellular responses. Synergistic effects of IL-1b, IL-6 and TNF-a on inflammatory and stress mediators [22] and IL-1b and IL-17 on chronic lung inflammation after viral infection [23] have been reported. In particular, the interaction between IL-1b and IL-6 in many types of inflammation [24][25][26] and the mechanisms of synergism [27][28][29] have been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were treated according to the Guide for the Care and Use of Laboratory Animals (NIH Publication No. 85- 23,1996), and the study was approved by the Animal Care Committee of Tokushima University. Influenza virus A/Puerto Rico/8/ 34 (H1N1) (PR8) was kindly provided by The Research Foundation for Microbial Diseases of Osaka University (Kagawa, Japan).…”
Section: Animals and Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors reported that IL-1β mediates virus-induced M2 muscarinic receptor dysfunction and airway hyper-reactivity during parainfluenza virus infection [218]. Data from the literature reported that IL-1β and IL-17A are key mediators of neutrophilic inflammation in influenzainduced exacerbations of chronic lung inflammation [219].…”
Section: Anti-interleukinmentioning
confidence: 99%
“…Interleukin-1β, angiotensin converting enzyme-1 and endothelin-1 genes were associated with more than 45% of these shared links (table 2), supporting the role of inflammation and vascular physiology as specific mechanisms underlying the pathobiology of comorbidities in COPD. Furthermore, these three genes have also been related with the pathogenesis of COPD [28][29][30][31][32][33][34], hence providing a link between comorbidities and COPD itself, as recently suggested by a model of COPD that identifies the lung, the bone marrow and the adipose tissue as a vascularly interconnected network of potential pathogenic relevance [35]. In this context, it is of note that the diseasome (clinical or molecular diseasome) presented here has a very prominent "vascular" component, which may reflect the fact that admissions for exacerbation of COPD can also have a significant cardiovascular component [36,37].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%